IMPLEMENTATION OF LEARNING MEDIA BY TEACHERS FOR YOUNG LEARNERS AT ANUBANWANGMAI SCHOOL, THAILAND - Zahra, Nur Az; Hardianto, Asep (Journal of Arts and Education, 2025)
This research is entitled “Implementation Of Learning Media By Teachers For Young Learners At Anubanwangmai School, Thailand” The background of this research is teachers who have an important role in the school education environment, especially when the learning process takes place. The teacher's method is used as a tool to achieve teaching goals, so the better the use of teaching methods, the more successful the achievement of goals. In other words, if the teacher can choose the right method according to the teaching material, students, situation, and teaching media, the more successful the teaching objectives will be achieved. According to observations and surveys conducted by researchers, the use of learning media and teachers is quite optimal. This can be seen from the learning carried out by teachers who have used interesting learning media. In addition, students become active in the learning process because of the interaction in the classroom and the tendency of students to remain active and dare to express opinions or questions. The purpose of this study was to determine the extent of teachers' perspectives on learning media as a tool that helps achieve learning objectives at Anubanwangmaisat school, Satun, Thailand. This study is a descriptive research data obtained by conducting observations and interviews with teachers at anubanwangmai sasanasart school, Thailand. The results of this study show that the importance of using learning media for young learners at anubanwangmai sasanasart school, Thailand.